Microbiome and metabolome explain the high-fat diet-induced diabetes development and diabetes resistance in Guizhou mini-pigs - Wu, Yanjun; Mo, Jiayuan; Wang, Qianguang; Li, Jialong; Wei, Jia; Zhang, Nuo; Dong, Yuanqiu; Zhu, Xiang; Lu, Taofeng; Huang, Sicheng (Frontiers in Microbiology, 2025)
Type 2 diabetes mellitus (T2DM) is an obesity-related disease claiming substantial global mortality annually. Current animal models of T2DM remain limited, with low success rates in establishing porcine models of high-fat diet (HFD)-induced T2DM. Our experimental design employed 35 Guizhou mini-pigs to develop a T2DM model via HFD induction, aiming to identify microbial and metabolic signatures associated with disease pathogenesis and resistance. At month 10, five individuals from the control (CTR), T2DM (DM), and T2DM resistant (anti-DM) groups were slaughtered, samples were collected, and relevant indices were measured. Metagenomics, metabolomics, and 16S rRNA sequencing were performed to identify microbes and metabolites linked to T2DM progression and resistance. Key findings demonstrated anti-DM group parameters-including metabolic indices (fasting blood glucose, insulin levels, HbA1c, IVGTT), histopathology (HE-stained pancreatic/hepatic tissues), microbial profiles (structural, compositional, functional), and metabolomic signatures-occupied intermediate positions between CTR and DM groups. Network analyses revealed: (1) Lactobacillus, L. amylovorus, fingolimod, polyoxyethylene sorbitan monooleate, thiamine, and atrazine in HFD-associated networks; (2) Limosilactobacillus reuteri, N-oleoyl-L-serine, tolbutamide, tetradecanoyl carnitine, 3′-sulfogalactosylceramide, and guggulsterone in T2DM resistance networks; (3) Ruminococcaceae NK4A214 group, diethyl phthalate, zingerone, enalapril, 5-hydroxytryptophol, 2′-deoxyinosine, icariin, and emetine in T2DM progression networks. These results further clarify the role of the gut microbiota and serum metabolites in the development of T2DM in the Guizhou mini-pig model.